The girl who left : from Croatia to the canefields - Gavranich, Debra (Wild Dingo Press, 2021)
Marija's idyllic early childhood on the beautiful Croatian island of Korčula is brutally disrupted by the invasion of the Italians and then the Nazis in 1941, bringing death and destruction. The devastation has left families struggling to survive years after the war has ended. In 1950 an opportunity arrives for 17-year-old Marija to escape the hunger and despair all around her by committing herself to a complete stranger in faraway North Queensland, through a proxy marriage. Taking the plunge, she leaves her family and friends, her culture and everything she has ever known, to sail 12,000 km to a future in a land where she knows nothing and no one, whose language she doesn't speak. Is it a chance for a better life? Will her husband be a good man? Will she ever see her family again? This is the true story of an incredibly courageous young woman who risks all in her quest to escape a still-traumatised Europe.